1979
DOI: 10.1063/1.325780
|View full text |Cite
|
Sign up to set email alerts
|

An infrared study of phase-III poly(vinylidene fluoride)

Abstract: Infrared spectra representative of crystalline regions of cast films of phase-III poly(vinylidene fluoride) (PVF2) have been obtained by absorbance subtraction techniques using a FT-IR instrument. The spectra contain more bands than previously reported and are not consistent with current models for the crystal structure. Several possible models and their relationship to the corresponding crystalline spectra of phase II and phase I are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(126 citation statements)
references
References 10 publications
6
119
1
Order By: Relevance
“…Infrared spectra were examined over a broad temperature range as an alternative means to elucidate the nature of the transition. In poly(vinylidiene fluoride), an -i absorption band near 510 cm has been assigned to a -CF 2 bending 11,12 mode within TTT segments of the chainl ; this band shifts to %530 cm -for the TGTG conformation' 1 2 The copolymer investigated -l here exhibits an absorption band at 506 cm that we initially considered characteristic of TTT segments; such attribution has also been made by Yamada et al 5 for a band observed at 310 cm 1 (pre--i sumably the same as our 506 cm band). However, as shown in Figure 7a, this band does not shift in wavenumber as the sample is…”
Section: Minimentioning
confidence: 99%
“…Infrared spectra were examined over a broad temperature range as an alternative means to elucidate the nature of the transition. In poly(vinylidiene fluoride), an -i absorption band near 510 cm has been assigned to a -CF 2 bending 11,12 mode within TTT segments of the chainl ; this band shifts to %530 cm -for the TGTG conformation' 1 2 The copolymer investigated -l here exhibits an absorption band at 506 cm that we initially considered characteristic of TTT segments; such attribution has also been made by Yamada et al 5 for a band observed at 310 cm 1 (pre--i sumably the same as our 506 cm band). However, as shown in Figure 7a, this band does not shift in wavenumber as the sample is…”
Section: Minimentioning
confidence: 99%
“…Figure 1 shows the FTIR spectra of PVDF blends with different weight fractions of SAN (PVDF/ SAN: a) 100/0; b) 90/10; c) 80/20; d) 70/30; e) 50/50; f) 20/80; g) 0/100) crystallized in DMF at 50°C. For PVDF, 3020 and 2980 cm -1 were attributed to the symmetrical and asymmetrical stretching vibration of CH 2 [16,24]. For SAN, two peaks at 2930 and 2850 cm -1 corresponded to the CH 2 vibration.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Vibrational bands at around 530 cm -1 (CF 2 bending), 615 and 765 cm -1 (CF 2 bending and skeletal bending) and 795 cm -1 (CH 2 rocking) refer to α-phase. Vibrational bands at around 510 cm -1 (CF 2 bending) and 839 cm -1 (CH 2 rocking) correspond to β-phase [16,23]. Figure 1 shows the FTIR spectra of PVDF blends with different weight fractions of SAN (PVDF/ SAN: a) 100/0; b) 90/10; c) 80/20; d) 70/30; e) 50/50; f) 20/80; g) 0/100) crystallized in DMF at 50°C.…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,24] The 1113 cm -1 relatively intense peak in films deposited by continuous CVP process is assigned to the c-phase. [27] In pulsed deposited CPV films, the 1113 cm -1 peak is absent and other c-phase [28]…”
Section: Molecular Structure Of Filmsmentioning
confidence: 99%